A cento anni dalla Marcia su Roma: Recensione a Jacobin Italia, (n. 16, autunno 2022), numero monografico. - Fiocco, Gianluca (Testo e Senso, 2023)
This review presents the recent monographic issue of Jacobin Italia on the fascist regime and its legacies in Italian society, questioning the relationship between Italians and the experience of the twenty-year dictatorship a century after the March on Rome.